2009
DOI: 10.5507/bp.2009.032
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decline in Erythrocyte Acetylcholinesterase Activity: Correlation With Oxidative Stress

Abstract: Background:Oxidative stress hypothesis offers a mechanism for the aging process and its involvement in other pathologies such as diabetes and neurodegenerative diseases like Alzheimer. AChE activity in erythrocytes may be considered as a marker of central cholinergic status. The present study was undertaken to (i) determine the activity of erythrocyte AChE as a function of human process (ii) correlate AChE activity with oxidative stress during human aging.Material and Methods: Blood was collected from healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…It should also be noted that this discovery corroborates with Jha and Rizvi's (2009) studies that observed correlation between the antioxidant capability and the AChE activity.…”
Section: Resultssupporting
confidence: 88%
“…It should also be noted that this discovery corroborates with Jha and Rizvi's (2009) studies that observed correlation between the antioxidant capability and the AChE activity.…”
Section: Resultssupporting
confidence: 88%
“…30 The determination of AChE activity in the erythrocyte membrane has been used as a free radical-mediated oxidative stress parameter during aging in humans. 31 Our results clearly show that the activity of AChE in the erythrocyte is significantly decreased in dense (senescent) erythrocyte (fraction 2) of young (4-month-old) rats in comparison to fraction 1 and un-fractionated erythrocytes of young rats. The pattern of decrease in AChE activity in young and senescent erythrocytes was the same in 24-month-old rats, but the level of enzyme activity was much lower in old rats compared to 4-month-old rats.…”
supporting
confidence: 54%
“…AChE has an essential role in acetylcholine-mediated neurotransmission. It is present in the cholinergic synapses in the central nervous system as well as in neuromuscular synapses where it rapidly hydrolyzes acetylcholine (Igisu et al , 1994; Jha & Rizvi, 2009). The determination of AChE activity in blood is a great consideration in the diagnosis of poisonings caused by reversible and irreversible inhibitors of this enzyme including pesticides (Bukowska & Hutnika, 2006).…”
Section: Introductionmentioning
confidence: 99%